Fuzzy Logic Approach for Mobile Robot in Intelligent Space - Mohd Shah, Hairol Nizam; Sulaiman , Marizan; Syed Salim , Syed Najib (2008)
This project introduces the fuzzy logic approach for mobile robot in intelligent space. There are three major algorithms involved. They are known as object classification, object tracking and obstacle avoidance. The inputs are received from cameras which are mounted at a ceiling. The main idea of the object classification is to classify object into three categories depending upon their colors; the categories are mobile robot, destinations and obstacle position. These categories are represented by X symbol with different colors. This system is to teach and train the mobile robot proceeding to destination without hitting the obstacle. The mobile robot is autonomous; that means, it could be pursuing to the target position automatically without user guided. In this project, fuzzy logic is use to guide the mobile robot direction until it reaches the target position. This system is generates in real-time and suitable for indoor environment applications. One of the unique advantages of this project is that it only uses, there only used a camera and image processing generated by the algorithms itself without additional sensor such as sonar or IR sensor.